Project management and team building comparison between Finland and Russia - Kinnunen, Henri (My University, 2011)
Project management and team leading in global production environment is more and more common profession for academically educated people in companies. Our eastern neighbour Russia offers for both Finnish and other companies still increasing markets, and it is likely that the amount of projects in Russia will still rise. This thesis is based on the study of project management and team building differences to Russian practice. Russia is a huge country were exists thousands of procedures to make business and handle issues. In this book, it is focused to find Russian specialities and problems per each project management knowledge area that project managers are likely to meet and solve when executing projects in Russia. Main focus in this study is in results part of the book, were each knowledge is analysed based on experts’ judgment, case project observations and literature. Also the case project team’s transformational leadership survey is analysed in results part of the book. Conclusions are explained in the last chapter were it is concluded that there is a huge demand for project management professionals in Russia and that almost all knowledge areas contain specialities that project managers need to know and be able to manage. It also shows the differences between Russian and Finnish team behaviour and expectations. A few hints and suggestions are also given to the case company about team building and leadership as well as to all project management knowledge areas.
Keywords: Project management; knowledge areas; team building; Russia; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|